(untitled) (Web of Teachers: Inderscience Research, 2024)
The highest levels of creativity are given only to chosen individuals. The brilliant teaching activity of such talented individuals in pedagogy is not always a common occurrence. One of the creative pedagogues who has reached such heights and excellence, if it is appropriate to say, is the composer and skillful performer Farxod Alimov.